"It Led to Great Advances in Science": What Teacher Candidates Know About the Holocaust. Issue 2 (4th March 2019) - Rich, Jennifer
Abstract: A quarter of a century has passed since lawmakers enacted the New Jersey Holocaust education mandate, and it seems responsible and timely to ask if it, the original Holocaust education mandate, actually encouraged substantive learning about the Holocaust. Despite repeated fanfare about the mandate and its inclusion in educational curricula throughout the state, no existing studies have tested its impact. To fill the gap, this article examines the effectiveness of the New Jersey Holocaust education mandate. It does this by reviewing and analyzing a survey of teacher candidates at a large public university in New Jersey to develop data on the knowledge and attitudes about the Holocaust. The teacher candidates comprised a pool whose primary and secondary education took place under the mandate and who intend to teach within the state-mandated framework. After a review of the current state of Holocaust education, the article examines the New Jersey mandate and curriculum more carefully. It then moves on to explore the results of a mixed-methods survey given to teacher candidates at a public university in that state to offer a measure of the mandate's success. Finally, it ends with implications for revisions of curriculum and instruction.